Hệ trợ giúp quyết định phục vụ công tác bồi dưỡng và đào tạo công chức - Khoa, Nguyễn Đăng (Journal of Computer Science and Cybernetics, 2016)
In this paper we shall introduce some characteristics, architecture and design of the Decision Support System (DSS) based on new technologies. The demand for applying a DSS in the public management in order to make reasonable decisions, solving non-structured or semi-structured problems is very high. We present also an experimentation of a DSS applied to training staff personals in the National Institute for Public Administration (NIPA).